2019
DOI: 10.1155/2019/6390182
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Infrapatellar Fat Pad and Synovial Membrane to Knee Osteoarthritis Pain

Abstract: Osteoarthritis (OA) is the most common form of joint disease and a major cause of pain and disability in the adult population. Interestingly, there are patients with symptomatic OA displaying pain, while patients with asymptomatic OA that do not experience pain but show radiographic signs of joint damage. Pain is a complex experience integrating sensory, affective, and cognitive processes related to several peripheral and central nociceptive factors besides inflammation. During the last years, the role of infr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
131
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(136 citation statements)
references
References 155 publications
(241 reference statements)
3
131
0
2
Order By: Relevance
“…Synovial inflammation, as one of the typical pathological features of OA, plays an important role in the development of OA [2,[5][6][7]11]. However, as of now, any article has been published on how to extract and identify exosomes in synovial tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Synovial inflammation, as one of the typical pathological features of OA, plays an important role in the development of OA [2,[5][6][7]11]. However, as of now, any article has been published on how to extract and identify exosomes in synovial tissue.…”
Section: Discussionmentioning
confidence: 99%
“…However, as of now, any article has been published on how to extract and identify exosomes in synovial tissue. Importantly, more and more researchers consider the synovial membrane and intra-articular fat pad as an anatomical unit in OA pathogenesis and pain, and inflammation of synovial membrane in the knee joint may play a central role in OA and affect not only cartilage but also intra-articular fat pad [7,29,30]. Moreover, previous team studies have shown that synovial inflammation may affect articular cartilage damage through the innate immune system, aggravating the course of OA [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synovial tissue is a two cell layers thick membrane containing mainly two kinds of cell populations: synovial tissue macrophages (type A cells) and fibroblast-like synoviocytes (type B cells) (Falconer et al, 2018). Infiltration of lymphocytes, mild in OA and extensive in RA, leads to tissue hyperplasia contributing to inflammation, neovascularization, cartilage degradation, and pain sensitization (Mor et al, 2005;Asif Amin et al, 2017;Belluzzi et al, 2019). Activated synovial fibroblasts are involved in cartilage damage, particularly in RA subjects, via production of IL-6, IL-8, and TNF-a.…”
Section: Synovial Tissuementioning
confidence: 99%
“…The characteristic features of OA include degradation of the cartilage and sclerosis of subchondral bone, with increased synovial inflammation playing a major role in the degenerative bone disease [1,3,4]. Pro-inflammatory mediators may be released by the infrapatellar fat pad to stimulate proliferation of inflammatory cells in the synovial membrane, driving peripheral and central sensitisation in knee osteoarthritis [5]. The major symptom of OA is pain, which eventually leads to disability with increasing disease progression [6].…”
Section: Introductionmentioning
confidence: 99%